Ecological aspects of the casque-headed frog Aparasphenodon brunoi (Anura, Hylidae) in a Restinga habitat in southeastern Brazil - Mesquita, Daniel Oliveira; Costa, Gabriel Corrêa; Zatz, Mariana G. (Phyllomedusa: Journal of Herpetology, 2004)
We describe some aspects of the ecology of Aparasphenodon brunoi, a species associated with bromeliads. We comment on the relationships of this species with bromeliad size, microhabitat use, diet and sexual dimorphism. This study was conducted on a Restinga habitat near Presidente Kennedy, state of Espírito Santo, southeastern coast of Brazil. When the animals were found inside the bromeliads, we measure bromeliad and head size of frogs. We analyzed stomach contents and determined the sex and reproductive condition. We found 17 individuals (58.6%) in bromeliad leafs, six (20.7%) in Cactaceae, three (10.3%) in liana and three (10.3%) on trunks. The correlation between head measurements and bromeliad size were high, indicating that animals apparently use bromeliads based on their size, which could be related to the minimization of water loss. The most common prey items were beetles, ants, and insect larvae, suggesting that the species is relatively generalist in prey consumption. Aparasphenodon brunoi showed significant sexual size and shape dimorphism with females having larger bodies than males (size) and females having tibia, eye diameter and SVL larger than males (shape), but larger sample size and more detailed ecological and life history data are needed to elucidate the factors that have led to sexual size dimorphism.